Decoding Environmental Politics: Industrialization, Indigenous Rights and Resistance Movements in India - Biswal , Debendra Kumar (South Asian Journal of Social Sciences and Humanities, 2021)
Purpose of the study: To critically examine global discourse of development and it’s dismissive of indigenous environmental knowledge and role of international indigenism in giving space for debate on environmental politics. Based on case study of anti-POSCO movement in Odisha in India, it has tried to sort out dichotomy of openness to change in quality of life of local communities versus role of reactionary forces restricting development. Methodology: This study is a qualitative anthropological study among the tribal and local communities displaced in three villages by the POSCO project in Odisha. Modernisation theory of development was critically examined through the use of both primary and secondary data; interview, observation, Focus Group Discussion of the community, policy makers and activists and content analysis.Main findings: In India, modernization theory of development has pushed to the debate on the way of development “development from below” versus “development from above”. The anti-POSCO movement in Odisha reveals politics of truth; it’s just an extension of other popular movements and anti-development. The truth is of double edged, a confrontation of law of land versus rights of the people, and displacement of a section of population vs. development. Applications of this study: This paper will help create positive hypothesis that the legal industrialization can be legalised for the sake of poverty eradication and livelihood promotion governance. Industrialization is not hegemony of developed countries rather relevance for economic growth and reduction of poverty to meet MDGs in underdeveloped ones. Originality of this study: The theoretical issues raised are inter-disciplinary, pure economics of industry and economic growth, anthropology of modernization and philosophy of social facts and truth. It has also critically correlated the socio-cultural, environmental and agricultural basis of protest to industrialization. The methodology is fieldwork-based observation, interview and focus group discussion. Results have been analysed through dependent and independent variables in ecological anthropology.